2014
DOI: 10.1021/jf500429r
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Ionization Mass Spectrometric Analysis of κ-Carrageenan Oligosaccharides Obtained by Degradation with κ-Carrageenase from Pedobacter hainanensis

Abstract: κ-Carrageenan was degraded with a novel κ-carrageenase isolated from Pedobacter hainanensis, which was first isolated from seaside soil under the stacks of red algae in Hainan province of China. The κ-carrageenase was detected with a molecular weight of ∼55 kDa estimated from SDS-PAGE and yielded enzymatic activity of 700.53 units/mg of protein under the conditions of pH 7.0 and 40 °C. Analysis of the degradation products by TLC and HPLC indicated that the enzyme degraded κ-carrageenan to sulfated oligosacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…The molecular ion [G4S-H] − is a disaccharide with composition An-G4S (422 Da). 41 This is consistent with the results of the TLC, which showed that Car19 could degrade -carrageenan to neo--carrabiose.…”
Section: Substrate Specificity and Degradation Productssupporting
confidence: 90%
“…The molecular ion [G4S-H] − is a disaccharide with composition An-G4S (422 Da). 41 This is consistent with the results of the TLC, which showed that Car19 could degrade -carrageenan to neo--carrabiose.…”
Section: Substrate Specificity and Degradation Productssupporting
confidence: 90%
“…Low-molecular-weight carrageenans have been demonstrated to be antiviral in nature (Kalitnik et al, 2013). Studies have confirmed the antiviral activities of ɩ-, κ-, λ-, μ-, and νcarrageenans extracted from Gigartina skottsbergii toward the herpes simplex viruses type 1 (HSV-1) and type 2 (HSV-2) during infection of murine astrocytes (Carlucci, Scolaro, & Damonte, 1999).…”
Section: Carrageenan: Structure and Biological Activitiesmentioning
confidence: 92%
“…Although this method requires special equipment, it does not form undesirable toxic by-products or high amounts of monosaccharides as observed in chemical hydrolysis. The enzymes used for specific hydrolysis to produce AOS and COS from red seaweed polysaccharide include α-agarase (EC 3.2.1.158) [ 33 ], β-agarase (EC 3.2.1.81) [ 24 ], β-porphyranase (EC 3.2.1.178) [ 34 ], β-galactosidase (EC 3.2.1.23) [ 35 ], κ-carrageenase (EC 3.2.1.83) [ 36 ], ι-carrageenase (EC 3.2.1.157) [ 37 ], λ-carrageenase (EC 3.2.1.162) [ 38 ], cellulase (EC 3.2.1.4) [ 39 ], and pectinase (EC 3.2.1.15) [ 40 ]. These enzymes are produced by microorganisms from many sources, including seawater, marine algae, marine mollusks, soil, and the human gut.…”
Section: Production Of Oligosaccharide From Red Seaweedmentioning
confidence: 99%
“…Furthermore, β-porphyranases hydrolyze the β-(1,4)-glycosidic bonds of the porphyran repetition moieties of galactose linked with G4S in agar and produce oligosaccharides with galactose residues at the reducing ends [ 41 ]. Carrageenases, on the other hand, are highly specific for hydrolyzing carrageenans to produce COS. For example, κ-, ι-, or λ-carrageenase only degrades κ-, ι-, or λ-carrageenan, respectively [ 36 , 42 ]. These enzymes specifically endo-hydrolyze the β-(1,4)-glycosidic linkage between AHG and galactose, producing a series of COS. Vanegas et al reported a reducing sugar yield of 18 g/L for Laminaria digitata under the enzymatic hydrolysis process at 37 °C for 24 h [ 43 ].…”
Section: Production Of Oligosaccharide From Red Seaweedmentioning
confidence: 99%